2020
DOI: 10.1097/mat.0000000000001251
|View full text |Cite
|
Sign up to set email alerts
|

Specific Considerations for Venovenous Extracorporeal Membrane Oxygenation During Coronavirus Disease 2019 Pandemic

Abstract: Extracorporeal membrane oxygenation (ECMO) is recognized as organ support for potentially reversible acute respiratory distress syndrome (ARDS). However, limited resource during the outbreak and the coagulopathy associated with coronavirus disease 2019 (COVID-19) make the utilization of venovenous (VV) ECMO highly challenging. We herein report specific considerations for cannulation configurations and ECMO management during the pandemic. High blood flow and anticoagulation at higher levels than usual practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Appraisal using the JBI checklist for cohort studies and case series suggested a high level of quality across the included studies for this review. All studies, except two [ 13 , 32 ], had scores above 8/10 (Additional file 1 : Table S2). A summary of the GRADE assessment for certainty of evidence is provided in Additional file 1 : Table S4.…”
Section: Resultsmentioning
confidence: 99%
“…Appraisal using the JBI checklist for cohort studies and case series suggested a high level of quality across the included studies for this review. All studies, except two [ 13 , 32 ], had scores above 8/10 (Additional file 1 : Table S2). A summary of the GRADE assessment for certainty of evidence is provided in Additional file 1 : Table S4.…”
Section: Resultsmentioning
confidence: 99%
“…In a monocentric observation study, 17% of COVID-19 patients with ECMO support developed pulmonary hemorrhage that required intervention. Three cases were successfully controlled by temporary disruption of heparin for few days, and in one case successful embolization of a pulmonary artery was performed [ 1 ]. Murgo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary hemorrhage is a recurring finding in patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections and has been reported in 17% of cases with severe coronavirus disease 2019 (COVID-19) on extracorporeal support [ 1 ]. Necrotizing pneumonia is strongly associated with the occurrence of pulmonary hemorrhage and severely elevated inflammatory markers and comes with a poor prognosis [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…1). [5,6,[12][13][14][15][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] After excluding 11 studies with overlapping information, we included twenty-two retrospective observational studies with 1896 patients in the meta-analysis. There were 20 single centre studies and two registry reports (Tables 1 and 2).…”
Section: Study Details and Demographicsmentioning
confidence: 99%
“…Appraisal using the JBI checklist for cohort studies and case series suggested a high level of quality across the included studies for this review. All studies, except two, [13,32] had scores above 8/10 (Supplementary Table 3). A summary of the GRADE assessment for certainty of evidence is provided in Supplementary Table 4.…”
Section: Assessment Of Study Qualitymentioning
confidence: 99%